THE LIGHT CURVES OF THEORETICAL ASTEROIDS' MODELS - Burlak, N. R.; Korniychuk, L. V.; Korobeynikova, E. A.; Koshkin, N. I. (Одеські астрономічні публікації, 2017)
On the basis of modeling of asteroids form is calculate the set of light curves for five laws of reflection.